Mortality among patients with low‐grade follicular lymphoma: A binational retrospective analysis. Issue 13 (13th April 2022) - Rajamäki, Aino; Hujo, Mika; Sund, Reijo; Prusila, Roosa E. I.; Kuusisto, Milla E. L.; Kuitunen, Hanne; Jantunen, Esa; Mercadal, Santiago; Sorigue, Marc; Sancho, Juan‐Manuel; Sunela, Kaisa; Kuittinen, Outi
Abstract : Background: The life expectancy of patients with follicular lymphoma (FL) has improved considerably since the introduction of rituximab. This study examined the proportion of deaths from progressive lymphoma and the impact of FL on survival compared with that in the general population. Methods: Altogether, 749 patients with grades 1 and 2 FL in 9 institutions between 1997 and 2016 were enrolled. Competing risk models were used to estimate the cumulative incidences of deaths from progressive lymphoma and from other reasons. Excess mortality was analyzed with respect to the corresponding background populations standardized for age and sex using the excess mortality model based on the penalized spline approach. Results: The median follow‐up duration was 69 months (range, 0‐226 months). The estimated 10‐year overall, disease‐specific, and net survival rates were 72.4%, 86.6%, and 86.4%, respectively. The cumulative incidence of deaths from progressive lymphoma was slightly smaller than that of other causes in the study population (estimated 10‐year cumulative incidences: 12.3% [95% CI, 9.6%‐15.3%] and 15.4% [95% CI, 12.2%‐18.8%], respectively). Excess mortality was observed for up to 10 years after diagnosis, and it slightly increased with time. Conclusions: Deaths from progressive lymphoma are nearly as common as deaths from other causes in FL patients during the rituximab era. Despite the improvements in survival, there was evidence of excess mortality resulting from FL for at least 10 years after diagnosis. Abstract : Deaths from progressive lymphoma are nearly as common as those from other reasons in patients with follicular lymphoma (FL) in the rituximab era. Despite the improvements in survival, there is evidence of excess mortality from FL for at least 10 years after diagnosis.